Marketing : real people, real choices - Solomon, Michael R.; Stuart, Elnora W. (Upper Saddle River, N.J : Prentice Hall, 2000)
Making Marketing Decisions; Understanding and Identifying Markets; Creating and managing a Product: Goods and Services; Assigning Value to the Product. Delivering the product; Communicating about the Product.
Keywords: Marketing; Marketing -- Vocational guidance